The Role of Brain-Derived Neurotrophic Factor in Irritable Bowel Syndrome - Konturek, Thomas Jan; Martinez, Cristina; Niesler, Beate; van der Voort, Ivo; Mönnikes, Hubert; Stengel, Andreas; Goebel-Stengel, Miriam (Frontiers in Psychiatry, 2021)
Several studies have implied a role of brain-derived neurotrophic factor (BDNF) in abdominal pain modulation in irritable bowel syndrome (IBS). The aim of this study was to establish BDNF protein expression in human colonic biopsies and showing variation in IBS compared to controls. BDNF protein and mRNA levels were correlated with IBS symptom severity based on the IBS-symptom severity score (IBS-SSS). Biopsies from the descending colon and IBS-SSS were obtained from 10 controls and 20 IBS patients. Total protein of biopsies was extracted and assessed by ELISA and Western Blot. Total mRNA was extracted and gene expression measured by nCounter analysis. In IBS patients, symptom severity scores ranged from 124 - 486 (mean±sem: 314.2 ± 21.2, > 300 represents severe IBS) while controls ranged from 0 - 72 (mean±sem: 27.7 ± 9.0, < 75 represents healthy subjects, p < 0.001). IBS patients reported significantly more food malabsorption, former abdominal surgery and psychiatric comorbidities. BDNF protein was present in all samples and did not differ between IBS and controls or sex. Subgroup analysis showed that female IBS patients expressed significantly more BDNF mRNA compared to male patients (p < 0.05) and male IBS-D patients had higher IBS symptom severity scores and lower BDNF mRNA and protein levels compared to male controls (p < 0.05). Scatter plot showed a significant negative correlation between IBS-SSS and BDNF mRNA levels in the cohort of male IBS-D patients and their male controls (p < 0.05). We detected a high proportion of gastrointestinal surgery in IBS patients and confirmed food intolerances and psychiatric diseases as common comorbidities. Although in a small sample, we demonstrated that BDNF is detectable in human descending colon, with higher BDNF mRNA levels in female IBS patients compared to males and lower mRNA and protein levels in male IBS-D patients compared to male controls. Further research should be directed towards subgroups of IBS since their etiologies might be different.